KEBEBASAN INDIVIDU DAN CAMPURTANGAN KERAJAAN DALAM KONTEKS EKONOMI ISLAM - Ab Ghani, Ab Mumin (Jurnal Syariah, 2019)
There are two extreme conventional approaches towards the freedom of market i.e. laissezfaire and socialist. The first believes that the market will be determined by supply and demands thus, a goverment has no right to intervence. The second views that the goverment should determine the market. Islam however, does not favour any of these two, but the approach is rather moderate than extreme. The writer elaborate the ways Islam treats individual freedom and the extent of govermental interference is allowed.There are two extreme conventional approaches towards the freedom of market i.e. laissezfaire and socialist. The first believes that the market will be determined by supply and demands thus, a goverment has no right to intervence. The second views that the goverment should determine the market. Islam however, does not favour any of these two, but the approach is rather moderate than extreme. The writer elaborate the ways Islam treats individual freedom and the extent of govermental interference is allowed.